The Relationship Between Family Support and Anxiety in Seventh-Grade Adolescent Girls Facing Menarche at SMP Negeri 9 Purwakarta - Suparmi, Suparmi; Maulani, Hilda Nurrifa (Jurnal Indonesia Sosial Sains, 2025)
Menarche is a crucial phase in the lives of adolescent girls that often triggers anxiety due to a lack of information and environmental support. Family support, especially from parents, plays a crucial role in helping adolescents adapt to this biological change. This study aims to analyze the relationship between family support and anxiety levels in seventh-grade female adolescents at SMP Negeri 9 Purwakarta. The research method used was descriptive correlational with a cross-sectional approach. The sample consisted of 70 female students selected using a total sampling technique. The research instruments were a family support questionnaire and the Hamilton Anxiety Scale (HARS). The results of the analysis using the Spearman Rank test showed a significant negative relationship between family support and anxiety (p < 0.05; r = -0.62). The higher the family support, the lower the level of anxiety in adolescent girls facing menarche.